Bacillus subtilis BS-15 Effectively Improves Plantaricin Production and the Regulatory Biosynthesis in Lactiplantibacillus plantarum RX-8 - Liu, Guorong; Nie, Rong; Liu, Yangshuo; Li, Xue; Duan, Jiaojiao; Hao, Xu; Shan, Yumeng; Zhang, Jingying (Frontiers in Microbiology, 2022)
Plantaricin is a broad-spectrum bacteriocin produced by Lactiplantibacillus plantarum with significant food industry application potential. It was found that the plantaricin production of L. plantarum RX-8 was enhanced when co-culturing with Bacillus subtilis BS-15. This study therefore set out to explore how B. subtilis BS-15 induces biosynthesis of plantaricin. The effect of co-culturing with B. subtilis BS-15 on cell growth, plantaricin production, QS signal molecules PlnA/AI-2 secretion, as well as plantaricin biosynthesis gene cluster and AI-2 synthesis associated gene expression, was investigated in bacteriocin-producer L. plantarum RX-8. When L. plantarum RX-8 and B. subtilis BS-15 were co-inoculated in MRS for 20 h at inoculum ratio of 1:1 (106:106 CFU/mL), the greatest plantaricin output (2048 AU/mL) was obtained, rising by 32-fold compared to mono-culture of L. plantarum RX-8. Additionally, co-culture increased PlnA inducing activity and AI-2 activity 8-fold and 1.14-fold, respectively, over mono-culture. RT-qPCR findings generated every four hours (4~32 h) demonstrated that B. subtilis BS-15 remarkably improved the transcription of plnABCD and plnEF, and increased pfs and luxS transcription, even when using 200 mM D-ribose, a kind of AI-2 inhibitor. Based on the above findings, co-culturing with B. subtilis BS-15 as an environmental stimulus could activate the plantaricin induction via the PlnA-mediated intraspecies QS system and the AI-2-mediated interspecies QS system. Moreover, the inducing effect of PlnA and AI-2 in co-culture was independent. Differential proteomics analysis of B. subtilis BS-15 in co-culture indicated that bacteriocin-inducing regulatory mechanism may be related to flagellar assembly, peptidoglycan biosynthesis, anaerobic respiration, glycine cleavage system or thiamin pyrophosphate biosynthesis.